2009
DOI: 10.1038/nature07820
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in a neural globin tunes oxygen sensing in wild Caenorhabditis elegans

Abstract: Behaviours evolve by iterations of natural selection, but we have few insights into the molecular and neural mechanisms involved. Here we show that some Caenorhabditis elegans wild strains switch between two foraging behaviours in response to subtle changes in ambient oxygen. This finely tuned switch is conferred by a naturally variable hexacoordinated globin, GLB-5. GLB-5 acts with the atypical soluble guanylate cyclases, which are a different type of oxygen binding protein, to tune the dynamic range of oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
191
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 132 publications
(193 citation statements)
references
References 28 publications
2
191
0
Order By: Relevance
“…Persson et al reported that C. elegans globin homology glb-5 turns oxygen sensing triggering downstream signaling molecules. Therefore, many different globins in the C. elegans genome potentially contribute to the complexity to O 2 responses of C. elegans (16). Although hNgb is the homolog of GLB-13, hNgb exhibit new function against hypoxia injury as well as oxidative stress resistance in vertebrate during the evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persson et al reported that C. elegans globin homology glb-5 turns oxygen sensing triggering downstream signaling molecules. Therefore, many different globins in the C. elegans genome potentially contribute to the complexity to O 2 responses of C. elegans (16). Although hNgb is the homolog of GLB-13, hNgb exhibit new function against hypoxia injury as well as oxidative stress resistance in vertebrate during the evolution.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the function of few of the globins is known. Recently, the function of globin-5, which encodes a neuronal globin protein, was identified by two research groups (15,16 (17).…”
Section: Introductionmentioning
confidence: 99%
“…NPR-1 modulates the O 2 sensing neurons AQR, PQR, and URX, which mediate avoidance of high O 2 and O 2 /CO 2 concentrations (21-11%) (17,(25)(26)(27). Not the variability in the NPR-1 receptor is responsible for the difference in foraging behavior between C. elegans strains, also the recently discovered globin, GLB-5, plays a role (15,17). GLB-5 is an O 2 sensing, hexacoordinated protein occurring naturally in two allelic variations: glb-5 (Haw) that was originally found in the C. elegans strain CB4856, isolated from an Hawaiian pineapple field, and glb-5 (Bri) that was discovered in the standard laboratory Bristol strain N2.…”
Section: Glb-5mentioning
confidence: 99%
“…In bold, the aa that were excluded to construct the new model for GLB-5 Haw are given. The extra aa that were left out in the previous model are colored in grey (15). (d) Structural overlay of GLB-26 and GLB-6.…”
Section: Glb-6mentioning
confidence: 99%
See 1 more Smart Citation